PERSPECTIVES ON THE CHALLENGES TO THE WATCHDOG FUNCTION OF THE MEDIA IN NIGERIA - EMMANUEL OMULA; ROSELINE OGBOLE (International Studies Journal)
The study sought to find out the challenges to the watchdog function of the media, and the impact of these challenges on democracy and the people. The study is anchored on Agenda Setting Theory of the Press. Library Research Method was employed to generate secondary data for the study. The study has shown that the media as a watchdog of the society cannot achieve desired result in Nigeria, because our institutions are weak, compromised or corrupt and power does not reside in the people. This means that, no matter how the media try to ensure accountability in government it can hardly succeed when our institutions are weak and compromised. The study has also shown that, weak institutions and the fact that power does not reside in the electorates, is gradually paving way for kakistocracy and centralization of power. This means that the Executive arm (President) is becoming too powerful. This is true in that findings revealed that, the Supreme Court in Nigeria will never remove a sitting President, however deeply flawed his election may be, because the judiciary is weak and corrupt. Again it was revealed that, INEC deliberately rigged the 2023 Presidential Elections because Amazon that was engaged to provide technical support said, there was no glitch with the result viewing portals on February 2023. This shows that both INEC and the Judiciary are weak and compromised. Institutions of the state will continue to remain weak and useless until people who work in such institutions do the right thing. Findings revealed that, both public and private media owners have a lot of influence on the media they operate and  these owners, have used their media organizations to: influence public opinion, which is also another form of impediment to the watchdog role of the media It was concluded that, the watchdog function of the media  cannot bring about the desired accountability, good governance and dividends of democracy  in  a country where the institutions are weak and power does not reside in the electorates .It was recommended that heads of the various institutions of the state should not be appointed by the President and our institutions must be allowed to function without fear or favour.